2017
DOI: 10.1051/0004-6361/201630091
|View full text |Cite
|
Sign up to set email alerts
|

On the projected mass distribution around galaxy clusters

Abstract: Aims. Gravitational lensing allows to quantify the angular distribution of the convergence field around clusters of galaxies to constrain their connectivity to the cosmic web. We describe in this paper the corresponding theory in Lagrangian space where analytical results can be obtained by identifying clusters to peaks in the initial field. Methods. We derive the three-point Gaussian statistics of a two-dimensional field and its first and second derivatives. The formalism allows us to study the statistics of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Equation (A.8) simply quantifies the boost imposed by the peak condition in the initial conditionsδ c,i . This is consistent with the perturbative approach of Codis et al (2017) who showed that gravitational evolution induces a non-linear bias at all multipoles proportional to the peak height ν, the amplitude of fluctuations σ 0 ∝ D(a) and the rescaled three-point function ξ (3) . The agreement between both approaches follows from the D(a)δ c,i ↔ σ 0 ν correspondence.…”
Section: A1 the Weakly Non-linear Regimesupporting
confidence: 91%
See 3 more Smart Citations
“…Equation (A.8) simply quantifies the boost imposed by the peak condition in the initial conditionsδ c,i . This is consistent with the perturbative approach of Codis et al (2017) who showed that gravitational evolution induces a non-linear bias at all multipoles proportional to the peak height ν, the amplitude of fluctuations σ 0 ∝ D(a) and the rescaled three-point function ξ (3) . The agreement between both approaches follows from the D(a)δ c,i ↔ σ 0 ν correspondence.…”
Section: A1 the Weakly Non-linear Regimesupporting
confidence: 91%
“…To first order, the non-linear evolution of mass shells sinking towards the centre of clusters induces a boost of power at all angular scales due to the contraction of the Lagrangian patch initially encompassing the mass fluctuations. When the density field is nearly Gaussian, only m ≤ 2 moments are affected by the peak constraint, as demonstrated in Codis et al (2017), while in the quasi-linear regime this paper also predicts, perturbatively, the achromatic boost. In the highly non-linear regime, a simple model based on the spherical collapse model was presented, and is found to be in good agreement with measurements on massive haloes extracted from the PLUS Dark Matter cosmological simulation.…”
Section: Redshift Mass Binmentioning
confidence: 53%
See 2 more Smart Citations
“…Using the multipolar expansion of 2-D matter distribution around galaxy clusters, this technique succeeded in highlighting both the elliptical shape of clusters (see e.g Clampitt & Jain 2016;Shin et al 2018),. and filamentary patterns at cluster outskirts(Dietrich et al 2005;Mead et al 2010;Gouin et al 2017;Codis et al 2017) from 2-D projected DM distribution.…”
mentioning
confidence: 99%